Clinical profile of pediatric patients with tuberculosis in a tertiary care centre in India - Kumar, Ashna; Ahmad, Javid; Bharti, Pooja; Bakshi, Vasundhara (International Journal of Contemporary Pediatrics, 2020)
Background: India has one of the highest TB burden globally. Children contribute a significant proportion of TB burden, in whom the diagnosis can be challenging because many childhood diseases mimic TB. Therefore, a high index of suspicion is required for early diagnosis of childhood tuberculosis to prevent poor outcome. Objectives was to evaluate the prevalence and profile of childhood tuberculosis cases and to determine the risk factors Methods: An observational cross-sectional study was conducted over a period of 6 months at a hospital in north India and the prevalence and profile of the children admitted with the clinical suspicion of tuberculosis was studied. Case specific diagnostic approach was used for diagnosis and the appropriate treatment was instituted. Results: The prevalence of childhood TB was 2.3% among hospitalized children. Of these, 66.5% were males and 33.49% were females. The majority of cases were more than 8 years. The history of contact was present only in 31.1%. Tuberculin skin test was positive in 53.11%. Pulmonary tuberculosis was the most common type of childhood tuberculosis (45.45%) followed by neurological tuberculosis (42.8%), abdominal tuberculosis (6.45%), tuberculous lymphadenitis (2.63%), others (2.61%). Malnutrition was a potent contributing factor present in 91.86%. The mortality rate observed in the study was 9.56%. Conclusions: Owing to the high burden of tuberculosis among pediatric population in India, there is an alarming need to develop more economical and advanced diagnostic methods for better patient management and above all there is urgent need of the hour to educate the masses about the transmission and risk factors for this disease.